2018
DOI: 10.3349/ymj.2018.59.4.519
|View full text |Cite
|
Sign up to set email alerts
|

Variants in the Gene EBF2 Are Associated with Kawasaki Disease in a Korean Population

Abstract: PurposeKawasaki disease (KD) is a mucocutaneous lymph node syndrome. It is mainly seen in young children under the age of five. KD is a multifactorial disorder that includes genetic variants. The present study investigated the association between KD and single nucleotide polymorphisms (SNPs) in the candidate gene early B cell factor 2 (EBF2), which is associated with inflammation markers.Materials and MethodsAn SNP analysis was performed by whole exon sequencing of the EBF2 gene. Our study comprised a total of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…EBF2, EBF Transcription Factor 2, is a non-basic, helix-loop-helix transcription factors belongs to the COE (Collier/Olf/EBF) family, has a well conserved DNA binding domain and plays a critical role in regulating osteoclast differentiation. Many diseases are related to abnormal regulation of EBF2, such as Kawasaki Disease 32 , Inguinal Hernia 33 and Kallmann Syndrome 34 , 35 . NFATC1, Nuclear Factor of Activated T Cells 1, plays a role in the inducible expression of cytokine genes in T-cells (especially in the induction of the IL-2 or IL-4 gene transcription) and regulates many important genes of osteoclast differentiation and function.…”
Section: Discussionmentioning
confidence: 99%
“…EBF2, EBF Transcription Factor 2, is a non-basic, helix-loop-helix transcription factors belongs to the COE (Collier/Olf/EBF) family, has a well conserved DNA binding domain and plays a critical role in regulating osteoclast differentiation. Many diseases are related to abnormal regulation of EBF2, such as Kawasaki Disease 32 , Inguinal Hernia 33 and Kallmann Syndrome 34 , 35 . NFATC1, Nuclear Factor of Activated T Cells 1, plays a role in the inducible expression of cytokine genes in T-cells (especially in the induction of the IL-2 or IL-4 gene transcription) and regulates many important genes of osteoclast differentiation and function.…”
Section: Discussionmentioning
confidence: 99%
“…Susceptibility genes for KD (5-16) HLA, HCP5, FCGR2A, BLK, SLC8A1, CD40, NMNAT2, DAB1, COPB2, NAALADL2, IGHV, ZFHX3, NFKBIL1, ERAP1, EBF2, CACNB2, LTA, and LEF1 SNP in SLC8A1 (calcium signaling pathway) can be proof for using calcineurin inhibitors in KD and LEF1) (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16) to the risk of cardiovascular disease in KD (TIAM1, NEBL, PLCB4/PLCB1, TUBA3C, SLC8A1, PELI1, KCNN2, TIFAB, and AGT) (8,12,(17)(18)(19)(20)(21)(22) and to the risk of intravenous immunoglobulin (IVIG) resistance (BCL2L11 and SAMD9L) (23,24). Involvement of the HLA region in susceptibility to KD has been controversial and has not been replicated across different ancestral groups.…”
Section: Related Risk and Referencesmentioning
confidence: 99%
“…Ying et al[49] also revealed the risk of rs987401919 and rs36071027 of EBF1 in coronary artery disease, which are also interacted with smoking and alcohol abuse, impact on blood pressure and lipid contents of patients. Bae et al[50] reported the result of EBF2 rs10866845 increased the risk of Kawasaki disease, the mucocutaneous lymph node syndrome. As for the influence of EBFs to cancers, Xu et al[51] demonstrated the promoting function of EBF1 to USP5, the increased expression of USP5 could promote the proliferation of colorectal cancer through stabilizing the translation elongation factor.…”
mentioning
confidence: 99%